Inventarisasi Serangga Predator (Coleoptera) di Lahan Pare (Momordica charantia) dan Kacang Panjang (Vigna sesquipedalis) di Ogan Ilir, Sumatera Selatan - Agustine, Sarah Dean; Aprilia, Phillia; Cindi, Aulia; Anisa Putri, Rizki Ana; Wati, Manila; Adelia, Elda; Umayah, Abu; Gunawan, Bambang; Arsi, Arsi (Seminar Nasional Lahan Suboptimal, 2022)
Agustine SD, Aprilia P, Cindi A, Putri RAA, Wati M, Adelia E, Umayah A, Gunawan B, Arsi A. 2022. Inventory of predatory insects (Coleoptera) on bitter melon (Momordica charantia) and long beans (Vigna sesquidpedalis) in Ogan Ilir, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 674-681. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Beetles (Coleoptera) are often known as an order of insects that have the greatest diversity of their species among other orders. Approximately about 25% pf the recognizable animals belong to the Coleoptera group, it is estimated that there are more than 100 families of Coleoptera that have been known by scientists, with a total 350,000 species. This study aimed to determine the number of predatory insect species of the order Coleoptera on the Bitter Melon (Momordica charantia) and Long beans (Vigna sesquipedalis) in Ogan Ilir, South Sumatra, Indonesia. In this survey, we conducted sampling on three lands located in Tanjung Seteko, Tanjung Pering and Timbangan in Ogan Ilir Regency, South Sumatra. In the process of identification we use the insect classification book and also sourced from the internet in order to identify insects correctly and measurably. There are 4 species of predatory insects of the order Coleoptera on the field of long bean plants (Vigna sesquipedalis) and the Bitter Melon plant land (Momordica charantia) in the village of Tanjung Seteko is obtained Cycloneda munda and Harmonia axyridis, in Tanjung Pering is also obtained Cycloneda munda and Harmonia axyridis, in Timbangan only one species of beetle Coleophora inaequalis was obtained, from all the three villages in Ogan Ilir Regency, South Sumatra, 4 species of beetles (Coleoptera) were found which acts as a predator consisting of Cycloneda munda, Coccinella transverselysis, Harmonia axyridis and Coelophora inaequalisn. For the highest number of predatory species are of the Coccinella transversalis species numbering 14 heads. In research the predatory insect Coleoptera is most commonly found in the field of Long Beans (Vigna sesquipedalis) for its habitat and niches. So that from  this research it is necessary to maintain the preservation of predatory insects of the order Coleoptera by not using chemical pesticides.